COVID-19 in Conflict: The devastating impact of withdrawing humanitarian support on universal health coverage in Yemen - Al-Awlaqi, Sameh (Public Health Pract (Oxf), 2020)
The authors warn that, in the context of Yemen, the closure of humanitarian lifesaving programmes and shifting support toward health security, i.e. to support COVID-19 response, at the expense of primary health care support, will undermine existing health system strengthening efforts, worsen the humanitarian crisis and will accentuate the impact of COVID-19. The authors urge the international community and the Government of Yemen to carefully consider a more comprehensive approach to support Yemen’s COVID-19 response while maintaining, and strengthening, essential public health services.